الإجارة المنتهية بالتمليك وعلاقتها بعقد الهبة في المصارف الإسلامي: دراسة مقارنة : Comparative Study of IMBT and Gift Contract in Islamic Banking - Tokan, Abdurrahman; Hidayat, Syamsul; Nirwana, Andri (Universitas Muhammadiyah Surakarta, 2025)
Ijarah Muntahiya Bittamlik is a form of Islamic finance combining the contracts of I zev and sale or gift. Under this contract, the tenant (customer) leases the property from the lessor (bank) for a specified period of time with the promise that ownership of the property will be transferred at the end of the I zev period either through sale or gift. This contract is an alternative to traditional loans that rely on usurious interest, making it compliant with Islamic law, which prohibits usury. A key benefit of the Ijarah Muntahiya Bittamlik contract is that it allows the customer to benefit from assets such as movables, cars or real estate without the responsibility of direct ownership and the associated costs such as maintenance of the large property during the lease period, as the ownership of the property remains with the lessor until the end of the lease term. The transfer of ownership of the property occurs at the conclusion of the contract in accordance with the terms of the agreement, which may be facilitated by means of a gift, thereby obviating the need for the purchaser to incur the expense of ownership. Alternatively, the property may be sold at a nominal price. This transfer of ownership is an integral component of the mechanism that underpins the investment objectives of Islamic banks, as it ensures that both parties adhere to Shari'ah regulations and Shari'ah judgements in financial transactions. The hibah contract is a favoured method for transferring ownership in such contracts, as the gift from the bank to the customer is legitimate and available, and does not require any additional consideration at the end of the term. Consequently, the utilisation of hibah as a mode of transferring property ownership is not only accepted but also favoured by customers seeking to circumvent the prohibition of riba. It is evident that the gift contract constitutes a viable solution to the issue of transferring ownership in Ijarah Muntahiya Bittamlik, as it is consistent with the principles of Islamic Sharia. This is achieved by enabling customers to utilise the leased property in the event of non-payment of the full amount, without the necessity of direct borrowing with prohibited Riba interest.